PENGARUH SIKAP KERJA, KEMAMPUAN DIRI DAN STRES KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA SIBOLGA - Abdul Rahman Lubis; Falexius .; Asmar Zunawi Harahap; Plenning Dalf T.; Abdul Kawi Siregar (Universitas Islam Sumatera Utara, 2020)
Problem of this study is how influence of job attitude on performance. How influence of self ability on performance. How influence of job stress on performance. How influence job attitude, self ability and job stress on performance. The purpose of this study to determine the effect of job attitude on performance. Determine the effect of self ability on performance. Determine the effect of job stress on performance. Determine the effect of job attitude, self ability and job stress on performance. Sample in the study is 60 employee. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job attitude variable has a positive and significant effect on performance. Self ability variable has a positive and significant effect on performance. Job stress variable has a positive and no significant effect on performance. Job attitude, self ability and job stress variable has a positive and significant effect on performance.